“River City”: Seriality and Everydayness. Interview with Kieran Hannigan - Episcopo, Giuseppe (SigMa - Rivista di Letterature comparate, Teatro e Arti dello spettacolo, 2019)
The topic to which the monographic issue of the journal is dedicated is explored in a long interview on River City with the BBC television producer Kieran Hannigan. River City is a drama series (2002–) set in a Glaswegian community; its storylines are based on the lives and the relationships of the main characters: people that inhabit the district of Shieldinch. The interview aimed at exploring how the events of everyday life are represented in a soap opera, how the sense of a common life is portrayed on screen, as well as at learning more about the creative process and its daily aspects.